Improving the process of auditory processing and speech decoding using the Neuroflow method in an 11-year-old CAPD patient - Ejsmunt-Wieczorek, Izabela (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2021)
Hearing disorders at the level of the central nervous system significantly affect the development of speech and language communication in children with CAPD. One of the methods aimed at improving the auditory functions, and thus the quality of speech understanding, is Active Auditory Training with the Neuroflow method. Its effectiveness will be discussed based on the example of a 10-year-old patient with hearing impairment.